Multiscale study of the effect of fly ash geopolymer on the fatigue cracking of cement stabilized macadam. (10th March 2023) - Shi, Shuang; Wang, Ning; Chen, Chengyong; Ma, Tao; Chen, Feng; Gu, Gonghui
Highlights: The fatigue damage evolution of P-CSM and FAG-CSM was monitored using AE technique. The physical and mechanical properties of mortar and ITZ in CSMs were investigated. Differences in fatigue mechanisms of P-CSM and FAG-CSM revealed by micro-methods. Abstract: Understanding of the correlation between the micro-composition and macro-mechanics of cement stabilized macadam (CSM) is crucial to an optimized design of cement-treated base (CTB) with improved crack resistance. In this study, acoustic emission (AE) technique was used to monitor the crack propagation of plain cement stabilized macadam (P-CSM) and fly ash geopolymer cement stabilized macadam (FAG-CSM) under cyclic loading. Experimental tests and characterizations, including such as nanoindentation, Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS), were further performed. The test results show that FAG-CSM has better fatigue performance than that of P-CSM; the AE counts, risetime/AE amplitude values (RA) and b -value can be used to assess the damage degree, cracking mode as well as the bulk modulus of cement composites. Interfacial transition zone (ITZ) is the weakest modulus area in CSM and the incorporation of fly FAG can effectively increase the indentation modulus of ITZ. The volcanic ash reaction of fly ash leads to the hydration of cement to produce more hydration products, which reduce the voidance within ITZ and thus improve the bonding between the aggregate and mortar, which supports the findings of the macro-mechanical analysis and AE monitoring of CSM.